Psychosocial Correlates Of Substance Abuse Among Women In A Psychiatric Facility In Nigeria - Ayenibiowo, Dr Kehinde O.; OYEYEMI, BABALOLA BUKOLA; Owoeye, Dr. O. O. (Advances in Social Sciences Research Journal, 2015)
Psychoactive drug use among the female folk is fast becoming a matter of concern in many countries with gradual increase in the number of female drug abusers. In Sub-Saharan Africa, drug abuse was a male issue hence very little research has carried out among women drug abusers. The objective of this study is to identify the psychosocial variables that are linked to drug abuse among women. The study was conducted among female patients with DSM V diagnosis of substance use disorders in the Federal Neuropsychiatric Hospital, Lagos, Nigeria. There age range between 18 and 56. Socio-demographic questionnaire was administered to assess age, marital status, educational and employment status of the participants. In addition, information on their history of drug use were collected. Also, Hospital Anxiety and Depression Scale were administered on all the participants. Data obtained were analysed with SPSS version 16. The results shows that most of the participants were single, unemployed and either students or graduates of tertiary institutions. The drugs they abuse were mainly alcohol, nicotine and cannabis. They were introduced to drugs by friends, started using drugs before the age of 25 and were motivated by the need to derive pleasure. Psychological assessment did not show high level of anxiety or depression among the participants. However, they reported that drug abuse had diminished their health, social and occupational status. The findings reveal the need to address the issue of substance abuse among female adolescents to prevent increase in the number of female drug abusers.